Association of Subjective Cognitive Decline With Progression to Dementia in a Cognitively Unimpaired Multiracial Community Sample. (7th March 2023) - Chapman, Silvia; Rentería, Miguel Arce; Dworkin, Jordan D.; Garriga, Stella M.; Barker, Megan S.; Avila-Rieger, Justina; Gonzalez, Christopher; Joyce, Jillian L.; Vonk, Jet M.J.; Soto, Elizabeth; Manly, Jennifer J.; Brickman, Adam M.; et al.
Abstract : Background and Objectives: This prospective study seeks to examine the utility of subjective cognitive decline (SCD) as a marker of future progression to dementia in a community-based cohort of non-Latinx White, non-Latinx Black, and Latinx individuals. Debate surrounds the utility of SCD, the subjective perception of decline in one's cognition before such impairment is evident in traditional neuropsychological assessments, as an early indicator of impending Alzheimer disease. Unfortunately, most studies examining SCD have been conducted in non-Latinx White samples and commonly exclude groups of individuals shown to be most vulnerable to dementia. Methods: Participants were enrolled into this cohort study from the Washington Heights–Inwood Columbia Aging Project if they were cognitively unimpaired, had baseline measurement of SCD, and self-identified as non-Latinx White, non-Latinx Black, or Latinx. SCD was measured as a continuous sum of 10 items assessing cognitive complaints. Competing risk models tested the main effects of baseline SCD on progression to dementia. Models were adjusted for age, sex/gender, years of education, medical comorbidity burden, enrollment cohort, and baseline memory test performance with death jointly modelled as a function of race/ethnicity. Results: A total of 4, 043 (1, 063 non-Latinx White, 1, 267 non-Latinx Black, and 1, 713 Latinx) participants were selected for this study with a mean age of 75 years, 67% women, and with a mean follow-up of 5 years. Higher baseline SCD was associated with increased rates of incident dementia over time in the full sample (hazard ratio [HR] 1.085, CI 1.047–1.125, p < 0.001) and within Latinx (HR 1.084, CI 1.039–1.130, p < 0.001) and non-Latinx Black individuals (HR 1.099, CI 1.012–1.194, p = 0.024). Discussion: Overall results of this study support SCD as a prodromal marker of dementia in a multiracial community sample, and in Latinx and non-Latinx Black individuals in particular. Because models examining the risk of dementia were adjusted for baseline memory test performance, the results support the idea that SCD, a subjective reflection of one's own current cognitive functioning, contributes information above and beyond standard memory testing. Current findings highlight the importance of carefully evaluating any memory concerns raised by older adults during routine visits and underscore the potential utility of screening older adults for SCD.